2014
DOI: 10.1021/np400908u
|View full text |Cite
|
Sign up to set email alerts
|

Strychnobaillonine, an Unsymmetrical Bisindole Alkaloid with an Unprecedented Skeleton fromStrychnos icajaRoots

Abstract: A reinvestigation of the roots of Strychnos icaja resulted in the isolation of a new bisindole alkaloid named strychnobaillonine (1) with original C-17-N-1' and C-23-C-17' junctions, in addition to sungucine, bisnordihydrotoxiferine, and strychnohexamine (2). Compound 1 showed potent activity against the chloroquine-sensitive 3D7 strain of Plasmodium falciparum in vitro with an IC50 value of 1.1 μM. The structures of the compounds were defined by detailed spectroscopic analyses, especially 1H and 13C NMR, DEPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Chemical investigation of Alstonia macrophylla bark led to the isolation of two new nitrogenous derivatives, alstoniaphyllines A (13) and B (14), a new indole alkaloid, alstoniaphylline C (15), and eight known alkaloids including alstonisine (16) [29]. Also, Tchinda et al [30] reported the isolation of a new bisindole alkaloid, strychnobaillonine (19), with original C-17-N-1′ and C-23-C-17′ junctions, in…”
Section: Indole Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical investigation of Alstonia macrophylla bark led to the isolation of two new nitrogenous derivatives, alstoniaphyllines A (13) and B (14), a new indole alkaloid, alstoniaphylline C (15), and eight known alkaloids including alstonisine (16) [29]. Also, Tchinda et al [30] reported the isolation of a new bisindole alkaloid, strychnobaillonine (19), with original C-17-N-1′ and C-23-C-17′ junctions, in…”
Section: Indole Alkaloidsmentioning
confidence: 99%
“…Fadaeinasab et al [33] isolated seven isoquinoline alkaloids from the bark of Actinodaphne macrophylla. ey display in vitro antiplasmodial activity against P. falciparum 3D7 with IC 50 values ranging from 0.05 to 3.11 μM for cycleanine (25), 10-demethylxylopinine (26), reticuline (27), laurotetanine (28), bicuculine (29), α-hydrastine (30), and anolobine (31), respectively. Compound 26 was found to be the most active.…”
Section: Phenanthroindolizine Alkaloidsmentioning
confidence: 99%
“…14). The alkaloids were active against the 3D7 strain of P. falciparum , and the trisindole 94 was also cytotoxic against WI-38 cells (SI < 10), whereas 93 was not cytotoxic at the highest tested concentration (10 µg/mL) [77]. Interestingly, while monomers of Strychnos alkaloids do not have antiplasmodial activity, polymerization increases the basic nature of the monomers and confers antiplasmodial potency.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Recently Tchinda, et al [ 1 ] reported the isolation of strychnobaillonine ( 1 ), an unsymmetrical bisindole alkaloid with an unusual skeleton from Strychnos icaja roots. The structure of this intriguing natural compound was established by means of a detailed spectroscopic analysis, using 1 H and 13 C NMR techniques, including DEPT, HSQC, COSY, NOESY, HMBC, and HRESIMS.…”
Section: Introductionmentioning
confidence: 99%